Transgenic expression of human C19MC miRNAs impacts placental morphogenesis - Mouillet, Jean-Francois (Placenta, 2020)
INTRODUCTION: The chromosome 19 miRNA cluster (C19MC) encodes a large family of microRNAs (miRNAs) that are abundantly expressed in the placenta of higher primates and also in certain cancers. In the placenta, miRNAs from this cluster account for nearly 40% of all miRNAs present in trophoblasts. However, the function of these miRNAs in the placenta remains poorly understood. Recent observations reveal a role for these miRNAs in cell migration, and suggest that they are involved in the development and function of the human placenta. Here, we examine the placenta in transgenic mice expressing the human C19MC miRNAs. METHODS: We produced transgenic mice using pronuclear microinjection of a bacterial artificial chromosome plasmid carrying the entire human C19MC locus and derived a homozygous line using crossbreeding. We performed morphological characterization and profiled gene expression changes in the placentas of the transgenic mice. RESULTS: C19MC transgenic mice delivered on time with no gross malformations. The placentas of transgenic mice expressed C19MC miRNAs and were larger than wild type placentas. Histologically, we found that the transgenic placenta exhibited projections of spongiotrophoblasts that penetrated deep into the labyrinth. Gene expression analysis revealed alterations in the expression of several genes involved in cell migration, with evidence of enhanced cell proliferation. DISCUSSION: Mice that were humanized for transgenically overexpressed C19MC miRNAs exhibit enlarged placentas with aberrant delineation of cell layers. The observed phenotype and the related gene expression changes suggest disrupted migration of placental cell subpopulations.